A new method to realize nonrational driving‐point functions. (30th January 2020) - Kumar, Abhimanyu; Ganguli, Souvik
Summary: This paper presents a new synthesis procedure for nonrational driving‐point functions by defining and using the G operator. The operator is defined, and its properties are explored. Applying the Stieltjes transform on the G operator, the Padé approximant or the continued fraction form of the nonrational network function can be achieved with reduced computational complexity. Thus, the classical Foster and Cauer form or other techniques may be applied to synthesize network functions. The application of this work is demonstrated by considering certain functions such as the square root, inverse tangent, logarithm, and Lambert's W function. A set of conditions called synthesis criteria is proposed, which should be satisfied by a nonrational function to be realizable. Abstract : A new G‐operator is presented and its properties are explored to synthesize nonrational network functions with reduced computational effort. The work is applied to certain functions like square root, inverse tangent, logarithm, and Lambert's W function. Synthesis criteria are proposed to be satisfied by nonrational functions to be realizable.